Some new band gaps and defect modes of 1D photonic crystals composed of metamaterials - Singh S.K.; Pandey J.P.; Thapa K.B.; Ojha S.P. (My University, 2025)
Some new band gaps are found in 1D photonic crystals (1D PC) composed of metamaterials (including negative-μ materials, negative-ε materials and negative refractive index materials). These band gaps are investigated by using the transfer matrix method. The properties (central frequency and width of the gap) of these new gaps are invariant with the scaling of the lattice constant and show weak dependence with the incident angles. These new gaps result from the dispersive properties of the metamaterials. A defect mode appears inside these new gaps upon the introduction of a defect layer. The spectral position of the defect mode is invariant upon the change of scale length and almost independent of incident angles. © 2007 Elsevier Ltd. All rights reserved.